Effect of Durian Fruit on Blood Pressure - Brigitta Olivia Sinulingga; Angwen Rial Huga; Laurencia Alimin (Indonesian Journal of Global Health Research, 2020)
Durian or Durio zibethinus is a tropical fruit originating from Southeast Asia. Durian is often known as "King of Fruits". In Asian countries, durian is widely used as traditional medicine such as antipyretic drugs, anti-malaria, treating skin diseases, jaundice, anti-inflammation, boosting the immune system, wound healing and so forth. In fact, several studies have proven the health benefits of durian fruit such as antimicrobial, ant diabetic, ant cholesterol, antioxidant, antiproliferative, antibacterial, antifungal, and others. The objective of this paper is to describe the effect of durian on cardiovascularespecially blood pressurewhich is still controversial. This paper use literature study involving 18 libraries both national and international journals or books. In conclusion, there are still many people who believe that consumption of durian causes hypertension or high blood pressure, whereas based on research, consumption of durian in a small amount does not affect blood pressure, only for patients with hypertension must be careful in consuming durian in large amounts. Keywords: durian, blood pressure, systolic, diastolic, heart rate